Application of Social Cognitive Theory on the Determinants of Tertiary Prevention Behavior and Its Impact on Blood Pressure among Elderly Individuals with Hypertension in Surakarta, Indonesia - Tania Febiola; Argyo Demartoto; Bhisma Murti; Revi Gama Hatta Novika; Erindra Budi Cahyanto; Anik Lestari (Journal of Health Promotion and Behavior, 2026)
Background: Hypertension is a noncommunicable disease that commonly affects older adults and may lead to serious complications. Effective hypertension control also depends on tertiary preventive behaviors. This study aimed to examine the reduction of hypertension through tertiary preventive behaviors and to analyze the direct and indirect effects of Social Cognitive Theory constructs on tertiary preventive behaviors and systolic blood pressure among older adults with hypertension. Subjects and Method: This cross-sectional study was conducted in Surakarta, Indonesia. A multistage random sampling technique was employed, resulting in the selection of seven community health centers (Puskesmas) and a total sample of 211 respondents. Data were collected using questionnaires that had been tested for validity and reliability. Multivariate data analysis was performed using path analysis. Results: Tertiary preventive behavior was directly and significantly influenced by behavioral skills (b= 0.26; 95% CI= 0.11 to 0.40; p = 0.001), reinforcement (b = 0.23; 95% CI = 0.10 to 0.36; p = 0.001), self-regulation (b = 0.16; 95% CI = 0.02 to 0.30; p = 0.021), observational learning (b = 0.18; 95% CI = 0.06 to 0.30; p = 0.003), and female sex (b= 0.12; 95% CI= 0.02 to 0.21; p = 0.013). Systolic blood pressure was directly and significantly associated with tertiary preventive behavior in a negative direction (b= −0.14; 95% CI= −0.27 to −0.02; p= 0.027), indicating that better tertiary preventive behavior was associated with lower systolic blood pressure. In contrast, body mass index (b= 0.19; 95% CI = 0.06 to 0.32; p = 0.003) and age (b= 0.21; 95% CI= 0.08 to 0.34; p= 0.001) showed positive associations with systolic blood pressure. Sex was not significantly associated with systolic blood pressure. Outcome expectations indirectly influenced tertiary preventive behavior through self-efficacy and subsequently through behavioral skills. Conclusion: Tertiary preventive behavior is influenced by key constructs of Social Cognitive Theory and plays an important role in reducing systolic blood pressure among older adults with hypertension.